P-Adic Monodromy and the Birch and Swinnerton-Dyer Conjecture. - Mazur, Barry (Contemporary Mathematics Ser., 1994)
Recent years have witnessed significant breakthroughs in the theory of p-adic Galois representations and p-adic periods of algebraic varieties. This book contains papers presented at the Workshop on p-Adic Monodromy and the Birch and Swinnerton-Dyer Conjecture, held at Boston University in August 1991. The workshop aimed to deepen understanding of the interdependence between p-adic Hodge theory, analogues of the conjecture of Birch and Swinnerton-Dyer, p-adic uniformization theory, p-adic differential equations, and deformations of Galois representations. Much of the workshop was devoted to ex.